A simple and accurate solution based on a laser sheet system for on line position monitoring of welding. (November 2015) - D'Emilia, G; Di Gasbarro, D; Natale, E
Abstract: A methodology is presented able to check on line that optimal settings of a vision system are reached and maintained for automatic geometrical measurement welding having a complicated shape. The simple optical measurement system is based on a laser sheet. The set calibration methodology appears very sensitive to little deviations from optimum setting and allows the measurement system to reach level of uncertainty adequate for automatic dimensional checking of welding, even though a simple measurement system is used. The effects of process variability on the method are also studied and quantitatively evaluated; practical solutions for on line use of the methodology are finally discussed.